Templated synthesis of 2D TiO2 nanoflakes for durable lithium ion batteries. (9th August 2022) - He, Yaxuan; Li, Haibo
Abstract : A facile method has been proposed to prepare 2D TiO2 nanoflakes with high cycling performance and stability. Abstract : In this work, 2D TiO2 nanoflakes were prepared by employing MXene as a sacrificial template as the anode for durable lithium ion batteries (LIBs). Essentially, the highly crystalline anatase TiO2 nanoparticles compacted together to form 2D nanoflakes. This novel structure not only helps to alleviate the volume expansion of TiO2 in the charging/discharging process, but also promotes the Li + diffusion. Furthermore, as an anode for LIBs, it provides a high initial discharge capacity of 610.3 mA h g −1 with a coulombic efficiency of 53.7% at 100 mA g −1 . After 100 cycles, the capacity still remains at 246.6 mA h g −1, which is very significant among all reported data under these certain conditions. Besides, the post morphology characterization demonstrates that the structure of the 2D TiO2 nanoflakes is very well maintained after 100 cycles at 100 mA g −1, promising high specific capacity upon cycling.